CoS Acicular Nanorod Arrays for the Counter Electrode of an Efficient Dye-Sensitized Solar Cell - Kung, Chung-Wei; Chen, Hsin-Wei; Lin, Chia-Yu; Huang, Kuan-Chieh; Vittal, R; Ho, Kuo-Chuan (ACS nano, 2012)
One-dimensional cobalt sulfide (CoS) acicular nanorod arrays (ANRAs) were obtained on a fluorine-doped tin oxide (FTO) substrate by a two-step approach. First, Co3O4 ANRAs were synthesized, and then they were converted to CoS ANRAs for various periods. The compositions of the films obtained after various conversion periods were verified by X-ray diffraction, UV–visible spectrophotometry, and X-ray photoelectron spectroscopy; their morphologies were examined at different periods by scanning electron microscopic and transmission electron microscopic images. Electrocatalytic abilities of the films toward I–/I3 – were verified through cyclic voltammetry (CV) and Tafel polarization curves. Long-term stability of the films in I–/I3 – electrolyte was studied by CV. The FTO substrates with CoS ANRAs were used as the counter electrodes for dye-sensitized solar cells; a maximum power conversion efficiency of 7.67% was achieved for a cell with CoS ANRAs, under 100 mW/cm2, which is nearly the same as that of a cell with a sputtered Pt counter electrode (7.70%). Electrochemical impedance spectroscopy was used to substantiate the photovoltaic parameters.